An explanatory study of motivation for maintaining buyer-seller relationships in the presence of the holdup problem - Yap, Derek Tzse Ming (2011)
The trends in grocery retailing have shifted the power base from suppliers to retailers. Retailers can delist supplier products and provide substantial benefits like issuing large orders and extending retail space for suppliers because of their market dominance and controllership of the assets pertinent to the relationship. Subsequently this dependency has created opportunities for retailers to holdup suppliers and squeeze substantial financial concessions out of suppliers. That said the copious evidence show many of these retailer and supplier relationships are highly cooperative and collaborative instead of being riddled with conflict. Multidiscipline scholarly research explains trust as the basis for retailer and supplier to continue the relationship. Retailers and suppliers are motivated to cooperate because there are plenty of opportunities to reciprocate and to balance losses in the near future. On the contrary, our analysis reveals that the basis the motivations for continuing a relationship is based on a calculative process and not a relational process. The key findings from the case studies are participants recognize trust as an important antecedent for parties to start a relationship but are dependent on the perceived reward, expert and coercive power in deciding whether to continue the relationship or not. This has alluded to the importance for retailers and suppliers to strategize investments in building the most relevant power or powers pertinent to the relationship. In effect, suppliers should look at making strategic behaviors that build the reward power and expert power of retailers along with their own coercive power.